Can resilience training improve well-being for people in high-risk occupations? A systematic review through a multidimensional lens. Issue 5 (3rd September 2021) - Brassington, Kate; Lomas, Tim
ABSTRACT: Background : Psychological resilience may be central to Positive Psychology as one way to face the dark side of life. But is resilience training universally effective? This paper initiates a systematic review of primary research on resilience training in high-risk occupations. Methods : Examined resilience training outcomes and conducted analysis from a multidimensional perspective. Results : Thirty-three papers totalling 10, 741 participants, 12 occupations, and eight countries. Although 81% (n = 118) of Principal Outcomes reaching statistical significance showed improved well-being, resilience training was less effective in populations with prior trauma exposure or already experiencing the negative sequelae of trauma. Conclusion : Given the moral imperative to adequately prepare people in high-risk occupations for exposure to adverse stressors, further research is recommended into improving the effectiveness of resilience training for those already with primary or vicarious trauma exposure; and whether such training should also be offered to close family and co-workers of people in high-risk occupations.